Sistemas de indicadores de qualidade de vida: análise das experiências de Belo Horizonte, Ontário, Porito, Chillán e Ovalle - Salas, Juan Carlos Guillén (Universidade Federal de São Carlos, 2005)
Researchers, public employees and technical person in charge of the Urban Planning, more and more, need instruments that serve as support in the process for taking decisions in the formulation of strategies and politics destined to the preservation or improvement of the social well-being. In that sense, considering the potentiality that presents the study of the Quality of Life for the development of those instruments, the present work has as objective to analyze and to criticize some experiences that tried to operate the study of the Quality of Life when it is applied in the activity of the Urban Planning. In such objective, a revision of the technicianscientific literature about Quality of Life was accomplished with the purpose of being formed a theoretical referential on the theme, referential necessary for taking place the persecuted analysiscritic. Still, it was accomplished the identification and presentation of four instruments that intended to analyze and to evaluate the Quality of Life in the environment urban, contemporaries instruments, located in different contexts: Brazil, Canada, Portugal and Chile. The study was concluded with a critic of the same ones, having used the following analysis categories: managements, objective, conception, dimensions, form of elaboration of the instrument, structure and spatial reach. As resulted of the work was found that, in the analyzed experiences, the study of the Quality of Life in the urban environment has been a concern of the partner between the public management and academic research with the objective of evaluating the social well-being to give support the process for taking decisions in the formulation of the strategies and politics necessaries for the preservation or improvement of that well-being. The Quality of Life in the urban environment, in such those experiences, it has been considered as synonym of the conditions of life of the population or as the combination of the conditions of life and satisfaction of the population with those conditions,. Conceptions that have been approached through a dimension objective-material-quantitative (conditions of life of the population) and other subjective-immaterial-qualitative one (satisfaction of the population), dimensions that have been resulted of a vision technical or academic. The instruments have been operated through different domains, variables and indicators. The indicators, mainly, they have been developed with an objective-quantitative character, the ones that have been leaned in some cases with a satisfaction research - subjective-qualitative character -. The instruments have been developed with capacity of application in form spatially disaggregated in function of the homogeneity of the groups of people. Such resulted have been opposed with the theoretical referential showed from the revision of the technician-scientific literature about Quality of Life showing some observations in the conception, complementarity of the dimensions and participation of the population in the construction of the instruments. The Quality of Life, in the literature, it is pointed as the level of satisfaction of the population in function of their condition of life, the one that is evaluated from the particular values of the same population in a physical context". Situation that distinguish the satisfaction and condition of life of the population as the two dimensions under the which it has to be examined (dimensions objective and subjective), dimensions that have to refer the same subjects and; the particular values of the population as the aspect under which the priorities of the same population might be reflected with the participation the same one in the construction of the instruments. Key words: Urban planning, Quality of urban life - index, Indicators of quality, Methods of evaluation.
Keywords: Planejamento urbano; Qualidade de vida urbana - índice; Indicadores de qualidade; Métodos de avaliação; ENGENHARIAS